Full-Scale Tests of Butt-Welded Splices in Heavy-Rolled Steel Sections Subjected to Primary Tensile Stresses - Bruneau, Michel; Mahin, Stephen A. (Engineering Journal, 1991)
Experimental results from full-scale testing of full and partial penetration butt-welded capacity. Qualitative explanations are given as to the cause of the observed failure. The splice with full penetration welds exhibited satisfactory strength and ductility. It is believed that a great amount of care must be taken in the execution of this weld type. Future research needs are examined.